Analisis Antarmuka Pengguna Dalam Sistem Surat Disposisi Online Melalui Evaluasi Heuristik - Herman Fauzi; Hilman Ginanjar (Prosiding Seminar Nasional Teknoka, 2024)
organizations, one of which is Muhammadiyah University, Prof. DR. HAMKA to switch to a digital mailing system. One form of innovation is the online letter disposition system, which enables the process of receiving, distributing and managing letters more quickly, efficiently and transparently compared to manual methods. This system reduces dependence on physical documents, thereby reducing the risk of document loss and speeding up the flow of communication between work units. However, for this system to be effective and comfortable to use, the usability aspect is an important key, because users expect ease in operating each feature. This research focuses on evaluating the usability of the online disposition letter system through a heuristic approach, to identify areas that still require improvement. The evaluation results show that although this system already has a relatively consistent interface structure, several features still need improvement, especially in the aspects of dashboard interactivity, display consistency, and flexibility in mail management. It is hoped that the recommendations resulting from this research can serve as a guide for developers in improving user experience, so that this system is able to support organizational operations more optimally.